Recommendations to maintain immune health in athletes - Walsh, N. P. (European Journal of Sport Science, 2018)
Numerous studies over the last 35 years report an increase in upper respiratory infection (URI) symptoms in athletes during periods of heavy training and competition. Challenges athletes face such as heavy exercise and life stress influence immune function via activation of the hypothalamic-pituitary-adrenal axis and the sympathetic nervous system and the resulting immunoregulatory hormones. Both innate and acquired immunity are often reported to decrease transiently in the hours after heavy exertion, typically 15-70%: prolonged heavy training sessions in particular have been shown to decrease immune function; potentially providing an `open window` for opportunistic infections. Whether the observed changes in immunity with acute strenuous exercise or periods of heavy training account for the increased susceptibility to URI symptoms remains contentious. Nevertheless, there is little doubt that URI symptoms hinder athletic training and competition; underpinning the need to identify the prominent risk factors and appropriate countermeasures. Recent studies have identified prominent risk factors, including: intensified training in the winter; long-haul travel; low energy availability; high levels of psychological stress and anxiety; and depression. Given the shared pathways and effector limbs for the body`s response to physical and psychological challenges, it is logical that psychological strain influences immunity and illness incidence in athletes under heavy training; indeed, stress and anxiety have recently been shown to modify the immune response to exercise. This mini-review provides new insights and evidence-based recommendations for coping with the various challenges that athletes encounter on immune health, including: heavy exercise; life stress; sleep disruption; environmental extremes and nutritional deficits.